Composite biological regenerated asphalt and preparation method thereof
By combining modified ZDC with activated lignin and bio-oil, the performance degradation problem of traditional recycled asphalt under ultraviolet and oxidative environments has been solved, achieving efficient anti-aging effects and cost reduction, making it suitable for composite bio-recycled asphalt in highway engineering.
Patent Information
- Application Number
- CN202511714603.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-21
- Publication Date
- 2025-12-19
- Estimated Expiration
- 2045-11-21
AI Technical Summary
Traditional recycled asphalt is prone to performance degradation due to ultraviolet radiation and oxidation during outdoor service. Existing anti-aging agents have limited functions and are difficult to work synergistically, leading to frequent pavement defects. Furthermore, bio-oil is easily oxidized and has poor compatibility with anti-aging agents.
The modified zinc diethyldithiocarbamate (ZDC) is compounded with activated lignin and bio-oil. ZDC achieves antioxidant effect by capturing free radicals, lignin absorbs ultraviolet light and captures free radicals with phenolic hydroxyl groups, and bio-oil supplements the light components. The three work synergistically to enhance anti-aging performance.
It significantly improves the anti-aging properties of composite asphalt, extends its service life, reduces production costs, meets the "dual carbon" target, and is suitable for large-scale industrial production.
Smart Images

Figure SMS_5
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials technology, specifically relating to a composite bio-regenerated asphalt and its preparation method. Background Technology
[0002] With the surge in demand for highway maintenance, the recycling of reclaimed asphalt pavement (RAP) has become one of the core directions of green transportation development. Reclaimed asphalt technology restores the road performance of aged asphalt by adding recycling agents, but traditional recycling agents (such as waste engine oil and diesel fractions) have poor anti-aging properties. During outdoor service, recycled asphalt is susceptible to re-oxidation of components and volatilization of light components due to factors such as ultraviolet radiation, oxygen, and temperature fluctuations. This leads to decreased penetration, increased softening point, and reduced ductility, ultimately causing pavement cracking, rutting, and other defects, shortening the service life of the pavement.
[0003] Existing research indicates that the core mechanisms of performance degradation in recycled asphalt include: 1. Oxidation: Saturated and aromatic components in asphalt are oxidized into gums and asphaltenes, resulting in a significant increase in molecular weight and hardening and embrittlement; 2. Ultraviolet aging: 280-400nm ultraviolet light accelerates the breakage of asphalt molecular chains, generating polar groups such as carbonyl and sulfoxide groups, which exacerbates the peeling of feedstock and asphalt; 3. Limited function of recycling agents: Traditional recycling agents can only "temporarily soften" aged asphalt, cannot inhibit subsequent aging processes, and have poor synergistic compatibility with anti-aging agents.
[0004] Currently, the industry is attempting to introduce anti-aging agents to improve the performance of recycled asphalt. For example, adding inorganic zinc-based nanomaterials (zinc-based antioxidants) alone can capture oxidative free radicals, but cannot resist ultraviolet radiation; adding lignin alone (biomass UV absorbers) can absorb ultraviolet light, but its antioxidant efficiency is low; and when these two are directly incorporated into asphalt, they are prone to agglomeration due to differences in surface energy, with a dispersion uniformity of ≤70%, making it difficult to exert a synergistic effect. At the same time, although bio-oil can achieve regeneration regulation through the supplementation of light components, its own easy oxidation and lack of optimized compatibility with anti-aging agents limit its application in high-performance recycled asphalt.
[0005] Therefore, there is an urgent need to develop a composite recycled asphalt system that combines the triple functions of "regeneration regulation, UV protection, and oxidation resistance". Summary of the Invention
[0006] To address the aforementioned technical problems, the present invention aims to provide a composite bio-regenerated asphalt. This composite bio-regenerated asphalt is composed of aged asphalt, modified zinc diethyl dithiocarbamate (ZDC), activated lignin, and bio-oil in proportion to weight. ZDC achieves antioxidant effects by capturing free radicals. Lignin absorbs ultraviolet light through its benzene ring structure and captures free radicals through its phenolic hydroxyl groups, achieving a synergistic function of anti-ultraviolet and antioxidant properties. Bio-oil replenishes the light components lost from the aged asphalt, reducing its penetration and softening point to achieve regeneration regulation. The synergistic effect of the three components significantly improves the anti-aging performance and regeneration effect of the composite asphalt.
[0007] To achieve the above objectives, the following technical solution is adopted: A composite bio-regenerated bitumen, comprising, by weight: 66-85 parts aged bitumen; 2-6 parts modified ZDC; 5-20 parts activated lignin; and 8 parts bio-oil; The modified ZDC is obtained by surface modification of zinc diethyldithiocarbamate with a silane coupling agent; The activated lignin is derived from lignin activated by glycerol.
[0008] According to the above scheme, the preparation method of the modified ZDC includes the following steps: ZDC and KH560 were mixed at a mass ratio of 100:(1-3), dispersed in an organic solvent, heated to 60-80℃, and stirred for 1-2 hours. After drying, modified ZDC was obtained. The "solvent-assisted low-temperature modification" method utilizes the weak interaction between the silanol groups of KH560 and the surface of ZDC to form a coating layer, thus solving the interfacial compatibility problem between organozinc and asphalt and avoiding the decomposition of ZDC at high temperatures (its melting point is approximately 171℃). The resulting modified ZDC exhibited a dispersion uniformity of ≥95% in asphalt, and the diameter of the agglomerated particles observed under an optical microscope was ≤2μm.
[0009] According to the above scheme, the method for preparing activated lignin includes the following steps: Add 5-8% glycerol to dry lignin and activate it by stirring at 150-160℃ for 30-40 minutes to obtain activated lignin. Lignin has a highly polar surface, poor compatibility with pitch, and is prone to agglomeration. At 150-160℃, the hydroxyl groups of glycerol molecules form hydrogen bonds or undergo a mild etherification reaction with the hydroxyl groups on the lignin surface, introducing lipophilic-polar transition groups to reduce the surface polarity of lignin and narrow the polarity difference with pitch. Ultimately, the activated lignin is uniformly dispersed in pitch, effectively solving the compatibility and agglomeration problems. Simultaneously, glycerol can enhance the interfacial bonding force with pitch, ensuring anti-aging properties.
[0010] According to the above scheme, the bio-oil is sunflower seed oil with a density of 0.9 g / mL and a flash point > 110℃.
[0011] According to the above scheme, the composite bio-recycled asphalt has a penetration (0.1mm) of 60-100 at 25℃; a ductility of ≥50cm at 15℃; and after aging in a rotating thin film oven (163℃, 5h), the penetration ratio is ≥50%, the mass loss is ≤0.8%, and the residual ductility is ≥20cm.
[0012] This invention also provides a method for preparing the above-mentioned composite bio-regenerated asphalt, which solves the problems of anti-aging agent agglomeration and poor compatibility with asphalt through the process of "ZDC pre-dispersion-lignin activation-step mixing-constant temperature development".
[0013] The preparation method of the above-mentioned composite bio-regenerated asphalt includes the following steps: (1) The modified ZDC was mixed with a portion of bio-oil and heated to disperse by shearing to obtain a ZDC-bio-oil dispersion; (2) The aged asphalt was heated and softened, and the remaining bio-oil was added and sheared and dispersed to obtain an aged asphalt-bio-oil mixture system; The ZDC-bio-oil dispersion and activated lignin shear dispersion were added sequentially to obtain a composite asphalt mixture; (3) The resulting composite asphalt mixture is developed at a constant temperature and then naturally cooled to obtain composite bio-regenerated asphalt.
[0014] According to the above scheme, in step (1), the modified ZDC and bio-oil are mixed at a mass ratio of 1:1.
[0015] According to the above scheme, the heating and shearing dispersion in step (1) includes shearing dispersion at 110-120℃ and 2000-3000r / min for 8-12min.
[0016] According to the above scheme, the D50 of the ZDC-bio-oil dispersion obtained in step (1) is ≤3μm.
[0017] According to the above scheme, in step (2), the aged asphalt is heated to 160-180℃ and kept warm for 30-40 minutes to soften it.
[0018] According to the above scheme, step (2) involves shearing and dispersing at 160-170℃ and 2000-3000r / min for 15-20 minutes to obtain an aged asphalt-bio-oil mixture system.
[0019] According to the above scheme, the ZDC-bio-oil dispersion and activated lignin in step (2) are added at intervals of 5-10 minutes.
[0020] According to the above scheme, step (2) involves high-speed shearing at 170-180℃ and 4000-6000r / min for 20-40min to obtain a composite asphalt mixture.
[0021] According to the above scheme, the isothermal development in step (3) includes stirring at 165-175℃ and 500-800r / min for 15-25min.
[0022] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) ZDC, as an organic zinc product, has a purity ≥97.5%, is in powder or crystalline form, and has a melting point of 171℃. Its dithiocarbamate group (-SC(=S)-NR2) in its molecular structure can capture ROO generated by asphalt oxidation through the lone pair electrons of the sulfur atom. HO Free radicals are eliminated, terminating the oxidation chain reaction. After modification with KH560, epoxy propoxy groups are introduced onto the surface, forming van der Waals forces with the aromatic components of the asphalt, improving the dispersion uniformity to over 95%. The benzene ring structure of lignin absorbs 280-400nm ultraviolet light (absorption rate ≥85%), and the phenolic hydroxyl groups assist in scavenging free radicals. After activation with glycerol, its lipophilicity is enhanced, forming weak coordination bonds with the sulfur atoms of ZDC, thus enhancing the synergistic anti-aging effect. Sunflower seed oil can replenish the light components lost from aged asphalt, and at the same time, as a dispersion medium for ZDC, it dissolves organic zinc salts to prevent agglomeration, achieving a dual function of "regeneration-dispersion". The synergy of these three factors extends the anti-aging life of the composite asphalt.
[0023] (2) Regenerated asphalt is prepared by compounding aged asphalt, antioxidant ZDC, lignin and bio-oil in parts by weight. The antioxidant function of ZDC complements the UV-antioxidant function of lignin. Compared with adding ZDC or lignin alone, the composite system has a higher retention rate of aging penetration and aging ductility, and the anti-aging efficiency is improved.
[0024] (3) Bio-oil not only adjusts the penetration and softening point of aged asphalt, but also assists in the dispersion of ZDC and lignin, solving the problem that "recycling agents only soften and do not resist aging". The service life of composite asphalt is longer than that of ordinary recycled asphalt.
[0025] (4) Lignin (derived from agricultural and forestry waste) and bio-oil are biomass raw materials that can replace some petroleum-based anti-aging agents, reduce production costs by 15-20%, and reduce pollution from the burning of agricultural and forestry waste, which is in line with the "dual carbon" goal.
[0026] (5) The preparation process uses conventional asphalt processing equipment (high-speed shearing machine, etc.), without the need for special equipment modification. The ZDC pre-dispersion, lignin activation and other steps are easy to implement on a large scale and are suitable for industrial mass production. Detailed Implementation
[0027] The following embodiments further illustrate the technical solution of the present invention, but are not intended to limit the scope of protection of the present invention.
[0028] A specific embodiment provides a composite bio-regenerated asphalt, the composition of which, by weight, is: 66-85 parts aged asphalt; 2-6 parts modified ZDC; 5-20 parts activated lignin; and 8 parts bio-oil. The modified ZDC is obtained by surface modification of zinc diethyldithiocarbamate with a silane coupling agent; and the activated lignin is obtained by activating lignin with glycerol.
[0029] Zinc diethyldithiocarbamate (ZDC), as a mature organic zinc product, has advantages such as high free radical scavenging rate, low cost, and good compatibility with organic systems, but it has not yet been applied in the field of asphalt recycling. This invention optimizes its dispersibility by utilizing KH560 modification, and through the synergistic anti-aging mechanism of ZDC and lignin, combined with the regeneration and dispersing assistance of bio-oil, it solves the pain points of traditional recycled asphalt: "regenerated asphalt is not resistant to aging, and resistant asphalt is difficult to disperse." This fills the application gap of organic zinc salts in asphalt recycling and provides a technical solution for the recycling of waste asphalt in harsh environments.
[0030] The zinc diethyldithiocarbamate used in this specific embodiment is an organozinc product with a purity ≥97.5%, in powder or crystalline form, and a melting point of 171℃. Its dithiocarbamate group (-SC(=S)-NR2) in its molecular structure can capture ROO generated by asphalt oxidation through the lone pair electrons of the sulfur atom. HO Free radicals are eliminated, terminating the oxidation chain reaction. After modification with KH560, epoxy propoxy groups are introduced onto the surface, forming van der Waals forces with the aromatic components of the asphalt, improving the dispersion uniformity to over 95%. The benzene ring structure of lignin absorbs 280-400nm ultraviolet light (absorption rate ≥85%), and the phenolic hydroxyl groups assist in scavenging free radicals. After activation with glycerol, its lipophilicity is enhanced, forming weak coordination bonds with the sulfur atoms of ZDC, thus enhancing the synergistic anti-aging effect. The bio-oil, made from sunflower seed oil, can replenish the light components lost from aged asphalt, and simultaneously serves as a dispersion medium for ZDC, dissolving organic zinc salts to prevent agglomeration, achieving a dual function of "regeneration-dispersion". The synergy of these three factors extends the anti-aging life of the composite asphalt.
[0031] The specific implementation also provides a method for preparing the above-mentioned composite bio-regenerated asphalt: Step 1: ZDC modification and pre-dispersion. The modified ZDC and bio-oil were mixed at a mass ratio of 1:1 and subjected to high-speed shearing at 110-120℃ and 2000-3000r / min for 8-12min to obtain a ZDC-bio-oil dispersion (D50≤3μm).
[0032] Step 2: Stepwise Mixing. Heat the aged asphalt to 160-180℃ and hold for 30-40 minutes to soften it. Add the remaining bio-oil (total bio-oil minus the amount used in Step 1). Stir at 160-170℃ and 2000-3000 rpm for 15-20 minutes to obtain the aged asphalt-bio-oil mixture. Add ZDC-bio-oil dispersion and activated lignin sequentially to the mixture (5-10 minutes apart), and shear at 170-180℃ and 4000-6000 rpm for 20-40 minutes. Stepwise mixing, first adding bio-oil to soften the aged asphalt, then adding ZDC dispersion and activated lignin sequentially, ensures that each component is dispersed layer by layer, avoiding stratification due to density differences.
[0033] Step 3: Constant temperature development. Maintain the sheared mixture at 165-175℃, stir at a low speed of 500-800r / min for 15-25min, and allow it to cool naturally to room temperature to obtain composite bio-regenerated asphalt.
[0034] The following specific embodiment provides a modified ZDC: ZDC and KH560 were mixed at a mass ratio of 100:2, dispersed in an organic solvent, heated to 60-80℃ and stirred for 1-2 hours, and then dried to obtain modified ZDC.
[0035] The following specific embodiment provides an activated lignin: Lignin (CAS No.: 8061-51-6) was purchased from Shandong Xiya Chemical Co., Ltd., with analytical grade AR, and appeared as a dark yellow-red or brownish-red solid. The lignin was dried at 105℃ for 2.5 h, and then 6% glycerol was added to the dried lignin. The mixture was then stirred and activated at 150-160℃ for 30-40 min to obtain activated lignin.
[0036] The bio-oil used in the following specific examples is sunflower seed oil with a density of 0.9 g / mL and a flash point >110℃.
[0037] Example 1 This embodiment provides a ZDC / lignin composite bio-regenerated asphalt. Its composition, by weight, is 85 parts aged asphalt, 2 parts modified ZDC, 5 parts activated lignin, and 8 parts bio-oil. The aged asphalt is obtained by long-term aging of the base asphalt, which is road-grade 90# asphalt.
[0038] Based on the raw material formulation of this embodiment, the specific preparation process of the ZDC / lignin composite bio-regenerated bitumen in this embodiment is as follows: Step 1: Mix the modified ZDC with an equal weight of bio-oil, and shear at 125℃ and 3500r / min for 12min to obtain a ZDC-bio-oil dispersion (D50=180nm). Step 2: Keep aged asphalt at 170℃ for 35 minutes, add the remaining bio-oil and stir at 165℃ and 2500r / min for 18 minutes; add ZDC-bio-oil dispersion (5 minutes apart) and activated lignin in sequence, and shear at 175℃ and 5000r / min for 30 minutes. Step 3: Maintain a constant temperature of 170℃, stir at 700r / min for 20min, and cool to room temperature.
[0039] According to JTGE20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering", aged asphalt and recycled asphalt were tested for three major indicators, rotational viscosity at 135℃, and rotational film heating test.
[0040] Comparative Example 1 This comparative example provides a ZDC composite bio-regenerated asphalt, whose proportions by weight are 90 parts aged asphalt, 2 parts modified ZDC, and 8 parts bio-oil. The specific preparation process of the ZDC composite bio-regenerated asphalt in this example is basically the same as that in Example 1.
[0041] Example 2 This embodiment provides a ZDC / lignin composite bio-regenerated asphalt. Its composition, by weight, is 83 parts aged asphalt, 4 parts modified ZDC, 5 parts activated lignin, and 8 parts bio-oil. The aged asphalt is obtained by long-term aging of the base asphalt, which is road-grade 90# asphalt. The specific preparation process of the ZDC / lignin composite bio-regenerated asphalt in this embodiment is basically the same as in Example 1.
[0042] Comparative Example 2 This comparative example presents a ZDC composite bio-regenerated asphalt. Its composition, by weight, is 88 parts aged asphalt, 4 parts modified ZDC, and 8 parts activated bio-oil. The specific preparation process of the ZDC composite bio-regenerated asphalt in this example is basically the same as in Example 1.
[0043] Example 3 This embodiment provides a ZDC / lignin composite bio-regenerated asphalt. Its composition, by weight, is 80 parts aged asphalt, 2 parts modified ZDC, 10 parts activated lignin, and 8 parts bio-oil. The specific preparation process of the ZDC / lignin composite bio-regenerated asphalt in this embodiment is basically the same as in Example 1.
[0044] Comparative Example 3 This comparative example provides a lignin-based bio-regenerated bitumen. Its composition, by weight, is 87 parts aged bitumen, 5 parts activated lignin, and 8 parts bio-oil. The specific preparation process of the lignin-based bio-regenerated bitumen in this example is basically the same as in Example 1.
[0045] Example 4 This embodiment provides a ZDC / lignin composite bio-regenerated asphalt. Its composition, by weight, is 78 parts aged asphalt, 4 parts modified ZDC, 10 parts activated lignin, and 8 parts bio-oil. The specific preparation process of the ZDC / lignin composite bio-regenerated asphalt in this embodiment is basically the same as in Example 1.
[0046] Comparative Example 4 This comparative example provides a lignin-based bio-regenerated bitumen. Its composition, by weight, is 82 parts aged bitumen, 10 parts activated lignin, and 8 parts bio-oil. The specific preparation process of the lignin-based bio-regenerated bitumen in this example is basically the same as in Example 1.
[0047] Comparative Example 5 Repeat Example 1, but replace the modified ZDC with an equal part by weight of ZDC, while keeping the rest unchanged.
[0048] Comparative Example 6 Repeat Example 1, but replace the activated lignin with an equal part by weight of lignin, while keeping the rest unchanged.
[0049] The performance test results of the recycled asphalt obtained in the above embodiments and comparative examples are shown in Table 1.
[0050] Table 1
[0051] As shown in Table 1, all embodiments meet the requirements of JTGF40-2004 specification and 25°C penetration of 60-100 (0.1mm) and 15°C elongation ≥20cm, and exhibit a better performance balance than the comparative example.
[0052] Example 1 achieved a ductility of 80-88 cm at 15°C, significantly better than Comparative Example 3 (60 cm) and Comparative Example 4 (55 cm) without ZDC (lignin alone is prone to embrittlement), and also higher than Comparative Example 1 (70 cm) and Comparative Example 2 (75 cm) without lignin, demonstrating the synergistic effect described in the patent; the softening point of Example 1 was 48-51°C, higher than that of the comparative examples (45-48°C), indicating that ZDC and lignin effectively improve high-temperature stability; simultaneously, the viscosity of all samples at 135°C was 1.6-2.3 mm. 2 / s, all satisfying "≤3mm" 2 The " / s" specification requires that the patented "ZDC pre-dispersion + lignin activation" process can avoid viscosity abnormalities caused by regenerator agglomeration and is compatible with conventional asphalt construction equipment.
[0053] The mass loss after TFOT in the examples was 0.38-0.45%, lower than that in the comparative example (0.48-0.55%). This is because ZDC captures asphalt oxidation free radicals and lignin blocks ultraviolet light, synergistically inhibiting the oxidation and volatilization of lightweight components, which meets the patented anti-aging mechanism of "terminating the oxidation chain reaction". The residual ductility of the examples was 52-62 cm and the residual penetration ratio was 76-80%, which not only far exceeded the standard requirement of "residual ductility ≥20 cm and residual penetration ratio ≥50%", but also significantly improved compared with the comparative example (residual ductility 30-46 cm and residual penetration ratio 65-72%). Among them, Example 2 (ZDC 4wt% + lignin 5wt%) had a residual ductility of 62 cm and a residual penetration ratio of 80%, reaching the optimal level of "penetration retention rate ≥75% and ductility retention rate ≥65% after TFOT", confirming the patent conclusion that "ZDC's antioxidant effect and lignin's UV protection work synergistically, and the anti-aging efficiency is better than that of a single anti-aging agent". The composite bio-recycled asphalt with anti-aging properties described in the patent can achieve dual compliance with road performance and anti-aging performance standards. Its penetration at 25℃, ductility at 15℃, softening point, and viscosity at 135℃ all meet engineering specifications. Moreover, the residual performance retention rate of TFOT after aging is significantly higher than that of a single anti-aging agent system, effectively solving the pain points of traditional recycled asphalt that are "not anti-aging after recycling and difficult to disperse after anti-aging".
[0054] In Comparative Example 5, the unmodified ZDC, lacking epoxy propoxy groups, could not form van der Waals forces with the asphalt aromatics, resulting in reduced dispersion uniformity. This led to a decrease in penetration to 70 (0.1 mm) at 25°C, a decrease in ductility to 72 cm at 15°C, and an increase in viscosity to 2.5 mm at 135°C. 2 / s, and unable to form weak coordination bonds with activated lignin, the residual penetration ratio decreased to 70% after TFOT, indicating that KH560 modification can ensure dispersibility and antioxidant properties, achieving a synergistic effect. In Comparative Example 6, the unactivated lignin had poor lipophilicity and low phenolic hydroxyl utilization, causing the ductility at 15℃ to decrease to 78cm, and the residual ductility after TFOT decreased to 50cm, proving that glycerol activation plays an important role in improving compatibility and anti-aging synergy. Comparative Examples 5 and 6 show that by modifying ZDC, activating lignin, and combining the regeneration regulation and auxiliary dispersion functions of bio-oil, the pain points of traditional recycled asphalt, "regenerated asphalt is not anti-aging, and anti-aging is difficult to disperse," are effectively solved, fully demonstrating the scientific nature of the patented technology principle. The synergistic effect of ZDC, lignin, and bio-oil is the core of the performance advantage. After ZDC is modified with KH560, the dispersion uniformity is improved, and after glycerol activation, the lipophilicity of lignin is improved. The two form weak coordination bonds to enhance the anti-aging effect, while bio-oil balances the regeneration and dispersion requirements. This is completely consistent with the patented "triple functional synergy" technical principle.
[0055] The preparation of composite bio-regenerated asphalt relies on conventional high-speed shearing equipment without special modifications. Furthermore, lignin and bio-oil (sunflower seed oil) are biomass raw materials, which reduces costs compared to traditional petroleum-based anti-aging agents while meeting the "dual carbon" target. Combined with its excellent anti-aging properties (extended service life compared to ordinary recycled asphalt), it has the potential for large-scale application in high-temperature / high-altitude / open-air road scenarios with strong ultraviolet radiation and harsh oxidation environments.
Claims
1. A composite bio-rejuvenated asphalt, characterized in that The components are as follows in parts by weight: 66-85 parts of aged asphalt; 2-6 parts of modified ZDC; 5-20 parts of activated lignin; and 8 parts of bio-oil. The modified ZDC is obtained by surface modification of zinc diethyl dithiocarbamate with a silane coupling agent. The activated lignin is obtained by activation of lignin with glycerol.
2. The composite bio-renewable asphalt as claimed in claim 1, wherein The preparation method of the modified ZDC comprises the following steps: ZDC and KH560 are mixed at a mass ratio of 100: (1-3), and then dispersed in an organic solvent, heated to 60-80℃, stirred for 1-2h, and dried to obtain the modified ZDC.
3. The composite bio-renewable asphalt as claimed in claim 1, wherein The preparation method of the activated lignin comprises the following steps: 5-8wt% of glycerol is added to dry lignin, and then stirred and activated at 150-160℃ for 30-40min to obtain the activated lignin.
4. The composite bio-renewable asphalt as claimed in claim 1, wherein The bio-oil is sunflower seed oil with a density of 0.9g / mL and a flash point of >110℃.
5. The method for preparing the composite bio-regenerated asphalt according to claim 1, characterized in that... The method comprises the following steps: (1) mixing the modified ZDC with part of the bio-oil, heating, shearing and dispersing to obtain a ZDC-bio-oil dispersion; (2) heating and softening the aged asphalt, adding the remaining bio-oil, and shearing and dispersing to obtain an aged asphalt-bio-oil mixture; sequentially adding the ZDC-bio-oil dispersion and the activated lignin, and shearing and dispersing to obtain a composite asphalt mixture; (3) constant temperature development of the obtained composite asphalt mixture, and natural cooling to obtain a composite bio-regenerated asphalt.
6. The method for preparing composite bio-regenerated asphalt as described in claim 5, characterized in that... In step (1), the modified ZDC and the bio-oil are mixed at a mass ratio of 1:
1.
7. The method for preparing composite bio-regenerated asphalt as described in claim 5, characterized in that... In step (1), the shearing and dispersing at elevated temperature comprises shearing and dispersing at 110-120℃ and 2000-3000r / min for 8-12min to obtain the ZDC-bio-oil dispersion.
8. The method for preparing composite bio-regenerated asphalt as described in claim 5, characterized in that... In step (2), the shearing and dispersing at 160-170℃ and 2000-3000r / min for 15-20min obtains the aged asphalt-bio-oil mixture.
9. The method for preparing composite bio-regenerated asphalt as described in claim 5, characterized in that... In step (2), the high-speed shearing at 170-180℃ and 4000-6000r / min for 20-40min obtains the composite asphalt mixture.
10. The method for preparing composite bio-regenerated asphalt as described in claim 5, characterized in that... In step (3), the constant temperature development comprises stirring at 165-175℃ and 500-800r / min for 15-25min.
Citation Information
Patent Citations
Special low-viscosity easy-dispersion regenerant for modified asphalt and preparation method thereof
CN102140253A
Lignin grafted magnesium aluminum-based layered double hydroxide modifier, anti-ultraviolet ageing asphalt and preparation method thereof
CN106700579A
Biological asphalt and preparation method thereof
CN107916122A
Permeable asphalt mixture
CN113636785A
Method for improving aging resistance of asphalt by nano enzymatic hydrolysis lignin and regenerating asphalt by nano enzymatic hydrolysis lignin
CN116376301A
Cited By
Composite biological regenerated asphalt curing agent and asphalt pavement curing method
CN121801342A
